Arms Trafficking - Ege, Gian; Schwarzenegger, Christian; Stempkowski, Monika (Carl Grossmann Verlag, 2022)
Trafficking in arms and weapons material is, perhaps, one of the most notorious forms of organised crime. Fuelled by both the movie industry as well as real world examples, criminal organisations are widely believed to engage in the trafficking of firearms and weapons material, including nuclear material. This illicit trade is further facilitated by corruption and other forms of collusion with government entities as well as by links between the criminal elements and the arms industry. As part of a joint teaching programme on transnational organised crime, students from the Universities of Queensland, Vienna and Zurich researched the topic of arms trafficking in a year-long course. Some of their academic papers are compiled in this volume, addressing topics ranging from international and national legal frameworks to levels and characteristics of this phenomenon in selected places, and enforcement and industry measures adopted to prevent and suppress this illicit trade.